Cutaneous manifestations in patients with COVID‐19: a preliminary review of an emerging issue. (1st September 2020) - Marzano, A.V.; Cassano, N.; Genovese, G.; Moltrasio, C.; Vena, G.A.
Summary: Background: The infection caused by the recently identified SARS‐CoV‐2, called coronavirus disease‐19 (COVID‐19), has rapidly spread throughout the world. With the exponential increase of patients worldwide, the clinical spectrum of COVID‐19 is being better defined and new symptoms are emerging. Numerous reports are documenting the occurrence of different cutaneous manifestations in patients with COVID‐19. Objectives: To provide a brief overview of cutaneous lesions associated with COVID‐19. Methods: A literature search was performed in the PubMed, Scopus and Web of Science databases up to 30 April 2020. This narrative review summarizes the available data regarding the clinical and histological features of COVID‐19‐associated skin manifestations. Results: The literature reports showed a great heterogeneity in COVID‐19‐associated cutaneous manifestations, as well as in their latency periods and associated extracutaneous symptoms. Pathogenic mechanisms are unknown, although the roles of a hyperactive immune response, complement activation and microvascular injury have been hypothesized. Based on our experience and the literature data, we subdivided the reported cutaneous lesions into six main clinical patterns: (i) urticarial rash; (ii) confluent erythematous–maculopapular–morbilliform rash; (iii) papulovesicular exanthem; (iv) chilblain‐like acral pattern; (v) livedo reticularis–livedo racemosa‐like pattern; and (vi) purpuric 'vasculitic' pattern. These six patterns can be merged into two main groups: the first – inflammatory and exanthematous – includes the first three groups listed above, and the second includes the vasculopathic and vasculitic lesions of the last three groups. Conclusions: The possible presence of cutaneous findings leading to suspect COVID‐19 puts dermatologists in a relevant position. Further studies are needed to delineate the diagnostic and prognostic values of such cutaneous manifestations.